2005
DOI: 10.1086/426446
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Signs and Symptoms with Pneumococcal Acute Otitis Media by Serotype--Implications for Vaccine Effect

Abstract: Introduction of the currently available pneumococcal conjugate vaccine is unlikely to result in a remarkable alteration in the clinical presentation of pneumococcal AOM in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…Serotype 19F has been associated with invasive infections in children and AOM with spontaneous otorrhea [24,32,68,69]. Furthermore, Palmu et al found serotype 19F as one of the most common pneumococcal serotypes recovered from samples of MEF and the serotype most often leading to earache [68,70]. In our study, carried 19F also had a high rate of resistance to at least one antibiotic (85.7%).…”
Section: Discussionsupporting
confidence: 56%
“…Serotype 19F has been associated with invasive infections in children and AOM with spontaneous otorrhea [24,32,68,69]. Furthermore, Palmu et al found serotype 19F as one of the most common pneumococcal serotypes recovered from samples of MEF and the serotype most often leading to earache [68,70]. In our study, carried 19F also had a high rate of resistance to at least one antibiotic (85.7%).…”
Section: Discussionsupporting
confidence: 56%
“…The presence of a purulent conjunctivitis gave a positive predictive value for H. influenzae AOM of 67% with an 86% negative predictive value. No useful predictors were found for M. catarrhalis AOM [34].…”
Section: Clinical Presentation and Identification Of Otopathogensmentioning
confidence: 86%
“…Some clinical signs have been associated with particular otopathogens (e.g. conjunctivitis is associated with H. influenzae, while more severe cases of AOM are more often caused by S. pneumoniae) [32][33][34]. However, accurate identification of underlying pathogens is not possible purely on clinical grounds.…”
Section: Clinical Presentation and Identification Of Otopathogensmentioning
confidence: 99%
“…pneumoniae remains the most frequently detected bacteria from patients with AOM in Asia, Africa, America and Europe. No significant differences between the clinical manifestations of AOM, resulting from the different pneumococcal serotypes, were identified but in general, PCV7 serotypes are reported to cause more otalgia or ear ache than non-PCV7-serotypes [ 123 ]. Additionally, children with AOM caused by S .…”
Section: Discussionmentioning
confidence: 99%